Occupational Hazard and Wage Compensating Differentials - Cousineau, Jean-Michel; Lacroix, Robert; Girard, Anne-Marie (The Review of Economics and Statistics, 1992)
This paper is the first study investigating wage-risk relationships for both fatal and nonfatal work-related accidents on the basis of a large occupational data bank. Risk variables cover the whole array of potential configurations found in the literature, while based on the compensated accidents over a four-year period for the province of Quebec. The authors first estimate the model using the standard techniques developed by previous researchers and then submit their initial results to additional tests that, in the past, had disturbing effects. It becomes apparent, however, that in all but one case the results remain positive and significant. Copyright 1992 by MIT Press.